VD_FINDINFO Jug / 2014 / 337 vom 5. Mai 2014 - VD Tribunal cantonal (2014)
IN DUBIO PRO REO, CONTRAINTE SEXUELLE, CONTRAINTEDROIT PÉNAL, TORT MORAL, FIXATION DE LA PEINE | 47 CO, 189 CP, 190 CP, 47 CP, 10 CPP (CH)